Germany : beyond the stable state - Kitschelt, Herbert; Streeck, Wolfgang, 1946- (Frank Cass, 2004)
This text offers an interpretation of recent German economic performance. The German capitalist model relies upon a cooperative relationship between organized labour and the employers. This relationship has started to break down. This book asks why.